In vivo assessment of vasa vasorum neovascularization using intravascular ultrasound: A comparison between acute coronary syndrome and stable angina pectoris. Issue 4 (April 2017) - Kume, Teruyoshi; Okura, Hiroyuki; Yamada, Ryotaro; Koyama, Terumasa; Fukuhara, Kenzo; Goryo, Yutaka; Kamata, Yasuhiko; Okamoto, Hiroshi; Tamada, Tomoko; Imai, Koichiro; Neishi, Yoji; Uemura, Shiro
Abstract: Background: Previous studies have suggested that vasa vasorum (VV) neovascularization plays an important role in the progression and vulnerability of coronary atherosclerotic plaque. Methods: A total of 130 patients with coronary artery disease including 75 acute coronary syndrome (ACS) cases and 55 stable angina pectoris (SAP) cases were studied. By using intravascular ultrasound (IVUS), VV was defined as a small (<1 mm) tubular or vesicular, low-echoic structure observed exterior to the media. Prevalence and maximal number of VV were compared between patients with ACS versus SAP. Results: The prevalence of VV at the culprit lesion was similar between the 2 groups (97% vs. 93%, p = 0.216). On the other hand, it was significantly higher in ACS than SAP at both reference sites (proximal: 93% vs. 81%, p = 0.047 and distal: 88% vs. 60%, p < 0.001, respectively). The maximum number of VV was significantly higher in ACS than in SAP (at the culprit lesion: 2.8 ± 1.3 vs. 1.8 ± 1.0, p < 0.001, at the proximal reference: 1.9 ± 1.1 vs. 1.3 ± 0.9, p = 0.003 and distal reference: 1.7 ± 1.1 vs. 1.1 ± 1.1, p = 0.003, respectively). Conclusions: VV neovascularization of coronary arteries was more enhanced in patients with ACS than in those with SAP, supporting its relation to plaque vulnerability. VV detected by widely used IVUS could be an adequate surrogate marker for plaque vulnerability in vivo.